NORMATIVE OBSERVATIONS OF DEEP SOIL MIXING TECHNOLOGY OF SOIL-CEMENT PILES MANUFACTURING (Academic journal Industrial Machine Building Civil Engineering, 2017)
This article deals with the complex process of pile foundation erection for civil building.Deep soil mixing (DSM) technology is used. In order to find material, necessary for theproper costing designing normative observations of DSM technology of RSCP manufacturingwere carried out using method of photo recording. Using that, labor spends of machines andworkers for a single unit of production as well as norm of time were calculated. Comparisonalgorithm that can be used for different techniques, conditions ways of constructionorganization and other factors is presented. This methodic allows determining of theinfluence of different factors of construction production and environment to the process ofRSCP manufacturing. Compiled results of this investigation and follows ones will allowadequate costing system for DSM technology to be created given that a necessary amount of apractical data will be accumulated.Keywords: pile, soil-cement, reinforcement, technology, costing, labor costs, timing,norm.